Is the Secure Base Phenomenon Evident Here, There, and Anywhere? A Cross‐Cultural Study of Child Behavior and Experts' Definitions. Issue 6 (15th March 2013) - Posada, German; Lu, Ting; Trumbell, Jill; Kaloustian, Garene; Trudel, Marcel; Plata, Sandra J.; Peña, Paola P.; Perez, Jennifer; Tereno, Susana; Dugravier, Romain; Coppola, Gabrielle; Constantini, Alessandro; et al.
Abstract : The evolutionary rationale offered by Bowlby implies that secure base relationships are common in child–caregiver dyads and thus, child secure behavior observable across diverse social contexts and cultures. This study offers a test of the universality hypothesis. Trained observers in nine countries used the Attachment Q‐set to describe the organization of children's behavior in naturalistic settings. Children ( N = 547) were 10–72 months old. Child development experts ( N = 81) from all countries provided definitions of optimal child secure base use. Findings indicate that children from all countries use their mother as a secure base. Children's organization of secure base behavior was modestly related to each other both within and across countries. Experts' descriptions of the optimally attached child were highly similar across cultures.